Optimization and evaluation of venturi tube reactors for non-thermal milk pasteurization using CFD method - Kimia Taki; Bahram Hosseinzadeh Samani; Sajad Rostami; Zahra Izadi; Firozeh Nazari (PLoS ONE, 2026)
With growing demand for preserving food’s nutritional and sensory qualities, non-thermal pasteurization methods like hydrodynamic cavitation in Venturi tubes offer an effective alternative to heat-based techniques. This study optimizes a Venturi reactor for milk pasteurization using computational fluid dynamics (CFD) with the k-ε turbulence model and response surface method (RSM). By adjusting throat diameter (4.91 mm), length (13.15 mm), and convergence/divergence angles (19.2°/8.31°), the design maximized turbulent kinetic energy (TKE) (0.2438 m²/s² peak, 0.0305 m²/s² average) and minimized energy loss (viscous dissipation 2.69 W, pressure drop 3483 Pa). Experiments confirmed a 2.91 log-reduction in E. coli , with negligible impact on milk’s fat, protein, and lactose, ensuring safety and quality.